ACR-ACNM-ASTRO-SNMMI Practice Parameter for Lutetium-177 (Lu-177) DOTATATE Therapy. (June 2022) - Love, Charito; Desai, Neil B.; Abraham, Tony; Banks, Kevin P.; Bodei, Lisa; Boike, Thomas; Brown, Richard K. J.; Bushnell, David L.; DeBlanche, Lorraine E.; Dominello, Michael M.; Francis, Tony; Grady, Erin C.; et al.
Abstract : Objectives: This practice parameter (PP) for Lutetium-177 (Lu-177) DOTATATE peptide receptor radionuclide therapy (PRRT) aims to guide authorized users in selection of appropriate adult candidates with gastroeneropancreatic neuroendocrine tumors (GEP-NETs) from foregut, midgut, and hindgut. The essential selection criteria include somatostatin receptor-positive GEP-NETs, which are usually inoperable and progressed despite standard therapy. Lu-177 DOTATATE is a radiopharmaceutical with high avidity for somatostatin receptors that are overexpressed by these tumors. This document ensures safe handling of Lu-177 DOTATATE by the authorized users and safe management of affected patients. Methods: The document was developed according to the systematic process developed by the American College of Radiology (ACR) and described on the ACR Web site (https://www.acr.org/Clinical-Resources/Practice-Parameters-and-Technical-Standards ). The PP development was led by 2 ACR Committees on Practice Parameters (Nuclear Medicine and Molecular Imaging and Radiation Oncology) collaboratively with the American College of Nuclear Medicine, American Society of Radiation Oncology, and Society of Nuclear Medicine and Molecular Imaging. Results: The Lu-177 DOTATATE PP reviewed pharmacology, indications, adverse effects, personnel qualifications, and required clinical evaluation before starting the treatment, as well as the recommended posttherapy monitoring, quality assurance, documentation, and appropriate radiation safety instructions provided in written form and explained to the patients. Conclusions: Lu-177 DOTATATE is available for therapy of inoperable and/or advanced GEP-NETs when conventional therapy had failed. It can reduce tumor size, improve symptoms, and increase the progression free survival. The PP document provides clinical guidance for authorized users to assure an appropriate, consistent, and safe practice of Lu-177 DOTATATE.